Level of knowledge about oral health of parents and its relationship with oral hygiene habits of their children from 8 to 10 years old - Clavijo Valladares, Alex Jair (2023)
Objective: To determine the relationship between the level of knowledge in oral health of parents with the oral hygiene habits of their children from 8 to 10 years old. Material and Methods: In this cross-sectional and prospective study, 200 parents and their 200 children of both sexes, students of Private Educational Institutions in the district of San Miguel, Lima -Peru, were surveyed. Two questionnaires were applied, one to determine the level of knowledge about oral health of the parents; and another to determine the oral hygiene habits of their children. The relationship between the level of knowledge about oral health of parents and the oral hygiene habit of their children was determined using the Mann Whitney U and Kruskal Wallis tests. The p < 0.05 specified the level of significance in both tests. Results: Most of the questionnaires were answered by the fathers (68.5%). 53% of the parents presented a good level of knowledge about oral health. Children who brushed 3 times a day and every day of the week showed a positive relationship with respect to the level of good knowledge of their parents.. Conclusion: The level of knowledge in oral health of the parents was not related to the oral hygiene habits of their children from 8 to 10 years of age. However, the level of good knowledge of the parents was related to a greater frequency of brushing of 3 times/day and every day of the week.